Decisions of the Supreme Court of Newfoundland : the reports, 1936-1940 - Newfoundland. Supreme Court (D. R. Thistle, Queen's Printer, 1952)
The decisions of the Supreme Court of Newfoundland and Labrador. Most volumes include both case and topical indexes. Alternative title from spine.